Nutrient dynamics in tropical rivers, lagoons, and coastal ecosystems of eastern Hainan Island, South China Sea - R. H. Li (Biogeosciences, 2014)
Nutrient dynamics based on field observations made along the eastern Hainan Island during the period 2006–2009 were investigated to understand nutrient biogeochemical processes, and to provide an overview of human perturbations of coastal ecosystems in this tropical region. The rivers showed seasonal variations in nutrient concentrations, with enrichment of dissolved inorganic nitrogen and dissolved silicate, and depletion of PO43−. High riverine concentrations of nitrate mainly originated from agricultural fertilizer inputs. The DIN : PO43− ratios ranged from 37 to 1063, suggesting preferential depletion of PO43− relative to nitrogen in rivers. Chemical weathering in the drainage area might explain the high levels of dissolved silicate. Aquaculture ponds contained high concentrations of NH4+ and dissolved organic nitrogen. The particulate phosphorus concentrations in the study area were lower than those reported for estuaries worldwide. The particulate silicate levels in rivers and lagoons were lower than the global average level. Nutrient biogeochemistry in coastal areas was affected by human activities (e.g., aquaculture, agriculture), and by natural phenomena including typhoons. The nutrient concentrations in coastal waters were low because of dispersion of land-derived nutrients in the sea. Nutrient budgets were built based on a steady-state box model, which showed that riverine fluxes are magnified by estuarine processes (e.g., regeneration, desorption) in estuaries and Laoyehai Lagoon, but not in Xiaohai Lagoon. Riverine and groundwater inputs were the major sources of nutrients to Xiaohai and Laoyehai lagoons, respectively, and riverine inputs and aquaculture effluents were the major sources for the eastern coast of Hainan Island. Nutrient inputs to the coastal ecosystem increased with typhoon-induced runoff of rainwater, elucidating the important influence of typhoons on small tropical rivers.